Assessment of retention characteristics of different attachments following new modifications (an in vitro study) - Mahabad Mahmud Saleh; Dhia Aldori (Erbil Dental Journal)
Background and objectives: This study aimed to compare the retention characteristics of different attachments used to retain partial dentures following new modifications. Methods: In this study three types of commonly used extracoronal castable attachments were selected, namely (1) Preci-verttix standard, CEKA attachment, (2) Preci-sagix mini size, CEKA attachment, (3) OT- cap normal, Rhein 83. They underwent simple modifications in order to improve their retention. A total of forty-two samples were prepared in three main groups. Each group subdivided into two subgroups with fourteen samples; 7 samples for non-modified and 7 for modified attachments. The tensile force was applied using a universal testing machine at a cross-head speed of 50 mm/min and maximum retention force at dislodgment was recorded. Strain and stress at dislodgement were calculated. Data were collected and analyzed using one- way ANOVA followed by Duncan test and finally paired ttest was performed for comparing the modified and non-modified attachments. Results: For all attachments, retention was increased significantly following modification except for OT-cap, which showed a non-significant reduction in retention. Modified Precivertix attachment was most retentive with the mean value of (48.893) Newton. For all attachments strain at dislodgement was increased after modification and highest mean value of (1.292) was recorded for Preci-sagix. Stress at dislodgement was increased following modification for all attachments, except Preci- vertix which showed significant reduction of stress. Conclusions: Modified Preci-vertix attachment showed the highest retention value with a significant reduction in stress.